KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN PRESTASI AKADEMIK SISWA DI SMA NEGERI DI YOGYAKARTA - Nur Sabila Rosyada; Nurkholifatul Maula (Balitbangda Provinsi Jambi, 2021)
Abstract The purpose of this study is to identify the principal's perspective on student academic achievement and the strategies carried out in the principal's transformational leadership to improve student academic achievement.This research conducted by qualitative research with research subjects from the principal, vice principal, teachers and students. Data collection techniques used in-depth interviews, documentation and observation studies. Test the validity of the data used source triangulation techniques. Data analysis techniques used qualitative data analysis.The results indicated that the principal had a goal to improve student academic achievement. Student academic achievement is focused on increasing national exam scores and the number of graduates entering tertiary institutions. The principal conducts a number of strategies to improve student academic achievement, including: conducting joint evaluations with school stakeholders to help shape the vision and mission of the school, the principal facilitating the teacher to attend workshops and training, the principal prepares an IT (Information and Technology) consultant or laboratory assistant to help teachers implement internet-based learning, principals provide opportunities for teachers to become resource persons at workshops or training, principals make regulations for teachers to play an active role in MGMP (Subject Teachers' Consultation), Principals involve parents in the process of formulating tutoring and evaluation of learning outcomes, principals collaborate with various figures and experts in various fields to be a resource in a cultural workshop program, Hold a tutoring program at the 0th hour for grade 11, tutoring class 12, tutoring on Saturdays, giving In the form of a free learning program, the school principal addresses the administrative problems of teachers through the MGMP, and the school principal conducts an evaluation workshop every semester. All strategies undertaken by the principal aim to improve student academic achievement. Keywords: Transformational Leadership, Principals and Academic Achievement of students.